Improving hand hygiene adherence in an endoscopy unit - Santos, L. X.; Souza Dias, M. B.; Borrasca, V. L.; Cavassin, L. T.; Deso di Lobo, R.; Bozza Schwenck, R. C.; Herrerias Puschiavo, T.; Toscano, C. M.; Hashiba, K.; Bierrenbach, A. L. (Endoscopy, 2013)
Background and study aims: Although hand hygiene is the most important measure in preventing infection transmission in healthcare settings, adherence to recommendations among healthcare workers is low. We implemented and assessed the impact of a World Health Organization-recommended educational intervention to improve hand hygiene adherence at the endoscopy unit of a Brazilian tertiary hospital. Patients and methods: Hand hygiene adherence and techniques used by healthcare workers of the endoscopy unit in the course of their duties were observed unobtrusively by four nurses from the infection control unit. Data were collected at every opportunity for hand hygiene. Evaluations were carried out before and 1 and 10 months after an educational intervention. The intervention consisted of task-orientated training sessions, with live demonstrations of the multitude of opportunities for hand hygiene and the appropriate techniques. In addition to assessing hand hygiene practices, we also evaluated staff knowledge through standardized questionnaires administered before and after the education intervention. Adherence was defined as hand hygiene/disinfection at an opportunity for hand hygiene.Results: Adherence improved from 21.4 % before the intervention to 63.3 % 1 month and 73.5 % 10 months after the educational intervention. Correct answers to the questionnaire were 82.1 % on pre-intervention test and 85.7 % on post-intervention test. Conclusion: Hand hygiene rates were low before the education intervention and improved significantly after it. Against expectations, adherence to hand hygiene practices had increased further at 10 months after the intervention, reinforcing the intervention’s positive impact.